A Sales Tax for Alberta Why and How - Ascah, Robert L. (Athabasca University Press, 2022)
The days of buoyant capital investment, jobs, and wealth are passing Alberta by as the boom-and-bust cycle runs its course and the global climate crisis becomes more acute. As the province scrambles to boost the dying oil economy and curb spending, one solution is all but ignored-a sales tax. In this collection, Alberta scholars and policy experts map out why and how a provincial sales tax can and should be implemented. They examine energy revenues, household incomes, and political support as well as opportunities for improving democracy and reducing the volatility of government revenues. Finally, this volume offers recommendations on structuring a consultative review process to improve Alberta's long-term fiscal sustainability. Contributions by Ergete Ferede, Ian Glassford, Kenneth J. McKenzie, Melville McMillan, Elizabeth Smythe, and Graham Thomson.